St. Thomas Aquinas, Dramatist? - Eric McLuhan (Studia Gilsoniana, 2016)
The article begins with the statement that there is one aspect of St Thomas’s work that has not received due scrutiny as a literary form, one with solid dramatic qualities and structure: the Article. The Article is as Thomistic as the syllogism is Aristotelian. This particular mode of argument was evidently original with St. Thomas: he did not derive it from the work of any other writer, yet its inner movement is of the essence of dialectic, from the opening proposition to opposing objections, then “to the contrary” position as found in orthodoxy, and then the writer’s resolution, and so on. It is a variation on the classic sic-et-non, a reasonable, balanced to and fro of the sort beloved by disputants. No parallel or even parody of this Article is to be found in any known literature before or since the thirteenth century. The author aims to show that part of the sheer power of the Article resides in the fact that it has two levels of operation. The surface is composed of the dialectical to-and-fro adumbrated above. But under that surface lies a rhetorical structure constructed along the lines of the five divisions of the rhetorical logos as laid out by Cicero and Horace.